Brown rice‐specific γ‐oryzanol as a promising prophylactic avenue to protect against diabetes mellitus and obesity in humans. Issue 1 (21st August 2018) - Masuzaki, Hiroaki; Kozuka, Chisayo; Okamoto, Shiki; Yonamine, Masato; Tanaka, Hideaki; Shimabukuro, Michio
Abstract: Chronic overconsumption of animal fats causes a variety of health problems, including diabetes mellitus and obesity. Underlying molecular mechanisms encompass leptin resistance, a decrease in rewarding effects of physical activities, xanthine oxidase‐induced oxidative stress in vasculature and peripheral tissue, impaired activation of incretin signaling, deviation in food preference, and dysbiosis of gut microbiota. Based on our clinical observation that daily intake of brown rice effectively ameliorates bodyweight gain, impaired glucose tolerance/insulin resistance and dependence on fatty foods in obese, prediabetes men, a line of research on brown rice (rice bran)‐derived γ‐oryzanol in mice experiments, cultured cells and human clinical trials is underway in our laboratory. Our works in mice showed that γ‐oryzanol, an ester mixture of ferulic acid and several kinds of phytosterols, acts as a molecular chaperone, thereby attenuating the strong preference for animal fats through suppression of endoplasmic reticulum stress in the hypothalamus. In pancreatic islets from both high‐fat diet‐induced and streptozotocin‐induced diabetic mice, γ‐oryzanol ameliorates endoplasmic reticulum stress and protects β‐cells against apoptosis. Noticeably, γ‐oryzanol also acts as a potent inhibitor against deoxyribonucleic acid methyltransferases in the brain reward system (striatum) in mice, thereby attenuating, at least partly, the preference for a high‐fat diet through the epigenetic modulation of striatal dopamine D2 receptor. Because dopamine D2 receptor signaling in the brain reward system is considerably attenuated in obese humans and rodents, γ‐oryzanol might represent a unique property to ameliorate both hedonic and metabolic dysregulation of feeding behavior, highlighting a promising prophylactic avenue to protect against metabolic derangement. Abstract : γ‐Oryzanol acts on brain hypothalamus and reward system, pancreatic islets, liver and adipose tissue, and gut micorbaiota with a unique and distinct property. GSIS: glucose‐stimulated insulin secretion, SCFA: short chain fatty acid, D2R: dopamine type 2 receptor, ER stress: endoplasmic reticulum stress.